CHARACTERISTICS OF ANALOG RICE BASED ON SAGO AND TARO FORTIFICATED WITH FISH OIL AS FOR FUNCTIONAL FOOD - Amanda Ariela Kalungga; Syahrul Syahrul; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aims to determine the analog rice formulation based on sago and taro with fortification of fish oil as a functional food. The treatments given consisted of (M3S, M5S) analog rice based on sagowith 3 and 5% fish oil fortification, (M3TS, M5TS) analog rice based on taro-sago with 3 and 5% fish oil fortification, and (M3T, M5T) analog rice based on taro with 3 and 5% of fish oil fortification. Analysis parameters include organoleptic test (appearance, taste, aroma, and texture), as well as proximate analysis. The best treatment combination is analog rice from sago fortified with fish oil as much as 5% with intact characteristics and creamy-yellowish color, the aroma no longer shows rancid from fish oil, tasteless, and a slightly fluffier texture. Protein value of 1.46% (db), water 9.45% (wb), ash content 4.25% (db), fat content 4.96% (db), crude fiber 18.66% (db), and total carbohydrates 68.13%.   Keywords : Analog rice, sago, taro, fish oil